THE ROLE OF EXPLORATIVE LEARNING IN IMPROVING BUSINESS PERFORMANCE - Tjahjaningsih, Endang; Maskur, Ali (Proceeding Fakultas Ekonomi, 2017)
The aim of the study was to analyze and describe the effect of explorative, transformative, and exploitative learning on business performance improvement through innovation. The population in the study was the owners/ managers of batik SMEs in Pekalongan City based on batik superior industry in Central Java Province which was is in mature condition with the the samples of 80 respondents. The results of the study show that explorative, transformative, and exploitative learning have a positive significant effect on innovation. Explorative learning has the greatest effect compared to transformative and exploitative learning. Furthermore, innovation has a positive significant effect on business performance. Keywords: Explorative, Transformative and Exploitative Learning, Innovation, and Business Performance